Older and more mindful? Age differences in mindfulness components and well-being. (3rd July 2021) - Mahlo, Leeann; Windsor, Tim D.
Abstract: Objectives: Empirical research on the processes through which mindfulness affects well-being is in its infancy. Furthermore, few studies have considered the positive effects of mindfulness on psychological functioning from a lifespan perspective. The present study aimed to examine the role of age in moderating associations of mindfulness components with well-being in the context of a proposed model of mindfulness. Methods: A community-based sample of 623 participants aged between 18 and 86 years ( M  = 48.78, SD  = 16.74) was recruited via an internet-based research platform. Participants completed questionnaire measures of mindful characteristics (i.e. present-moment attention, nonjudgment, interoception, acceptance, nonattachment, and decentering), flexible goal adjustment, and well-being. Results: Parallel mediation analyses showed that both present-moment attention and nonjudgment provided significant pathways to (a) flexible goal adjustment through nonattachment and decentering; and (b) well-being through acceptance, nonattachment, and decentering. Furthermore, present-moment attention, nonjudgment, acceptance, nonattachment, and decentering were all positively associated with age. Conditional process analyses revealed that the direct relationships between (1) present-moment attention and well-being, (2) nonjudgment and well-being, and (3) decentering and flexible goal adjustment became stronger with age and were significant for adults from around 40 years of age and older. Conclusions: The findings suggest that the tendency to focus on the present-moment and adopt a nonjudgmental orientation may become especially important for well-being with advancing age, and the ability to appreciate the transitory nature of personal experiences may be particularly important for flexible employment of both goal disengagement and reengagement strategies across the second half of life.